Serotypes of attachment pili of enterotoxigenic Escherichia coli isolated from humans. - Deneke, C F (1981)
Pili from enterotoxigenic Escherichia coli isolated from humans have been partially purified, and antisera have been prepared. These pili were initially attached to erythrocytes and then removed by thermal elution for purification. Three distinct antigenic types of pili have been identified. Antisera against these three pili types reacted with 60 of 106 (56%) enterotoxigenic E. coli isolated from humans but not with nontoxigenic, normal human fecal isolates of E. coli nor with enterotoxigenic E. coli strains isolated from animals. There was no correlation between pili serogroup and any of the following toxin production (heat labile, heat stable, or both), O antigenic type, geographical source of isolation, or mannose-resistant hemagglutination patterns of various erythrocyte types.